The Italian infinitive introduced by a determiner and its interpretation in Bulgarian translation - Ladovinska, Maria (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The article examines the constructions of the infinitive preceded by a determiner in Italian and their translation into Bulgarian. Using a corpus of examples, the constructions will be examined from both a structural and functional perspective. Examples from the corpus will serve to distinguish four types of constructions and describe their syntactic characteristics. Analysis of the published Bulgarian translation of the examples from the corpus will complement the discussion and reflections on both the Italian construction and the means by which it could be translated into Bulgarian.